Wireless Network Design at Pamekasan Regency Public Library - Fauzan Prasetyo Eka Putra; Moh. Irfan; Mohammad Aziz; Rama Nurja Saputra (Brilliance: Research of Artificial Intelligence, 2025)
The increasing demand for internet access in public service spaces, such as libraries, necessitates a reliable and efficient wireless network. This study aims to design a wireless network for the Pamekasan Regency Public Library to enhance user experience in accessing digital resources. The methodology includes a site survey, analysis of user needs, simulation of access point (AP) placement using Ekahau software, and evaluation based on signal strength, coverage, and user traffic. The study was conducted across three types of libraries: public, school, and campus libraries in Pamekasan. Each location was assessed for building structure, user density, and interference sources. The simulation results determined optimal AP placement, utilizing dual-band (2.4 GHz and 5 GHz) access points to achieve minimum signal levels of -67 dBm and a Signal-to-Noise Ratio (SNR) above 25 dB. The findings indicate that the proposed network design can provide stable, wide-ranging wireless access in all key service areas. This study concludes that effective network design, based on detailed site surveys and technical simulations, is crucial for supporting digital library services. The proposed design contributes to improving information access and is expected to serve as a reference for similar implementations in other public institutions.